Receptor-specific inhibition of GABA(B)-activated K+ currents by muscarinic and metabotropic glutamate receptors in immature rat hippocampus - Sohn, Jong-Woo; Lee, Doyun; Cho, Hana; Lim, Wonil; Shin, Hee-Sup; Lee, Suk-Ho; Ho, Won-Kyung (BLACKWELL PUBLISHING, 2007)
It has been shown that the activation of G(q)-coupled receptors (G(q)PCRs) in cardiac myocytes inhibits the G protein-gated inwardly rectifying K+ current (I-GIRK) via receptor-specific depletion of phosphatidylinositol 4,5-bisphosphate (PIP2). In this study, we investigated the mechanism of the receptor-mediated regulation of I-GIRK in acutely isolated hippocampal CA1 neurons by the muscarinic receptor agonist, carbachol (CCh), and the group I metabotropic glutamate receptor (mGluR) agonist, 3,5-dihydroxyphenylglycine (DHPG). I-GIRK was activated by the GABA(B) receptor agonist, baclofen. When baclofen was repetitively applied at intervals of 2-3 min, the amplitude of the second I-GIRK was 92.3 +/- 1.7% of the first I-GIRK in control. Pretreatment of neurons with CCh or DHPG prior to the second application of baclofen caused a reduction in the amplitude of the second I-GIRK to 54.8 +/- 1.3% and 51.4 +/- 0.6%, respectively. In PLC beta 1 knockout mice, the effect of CCh on I-GIRK was significantly reduced, whereas the effect of DHPG remained unchanged. The CCh-mediated inhibition of I-GIRK was almost completely abolished by PKC inhibitors and pipette solutions containing BAPTA. The DHPG-mediated inhibition of I-GIRK was attenuated by the inhibition of phospholipase A(2) (PLA(2)), or the sequestration of arachidonic acid. We confirmed that DHPG eliminated the inhibition of I-GIRK by arachidonic acid. These results indicate that muscarinic inhibition of I-GIRK is mediated by the PLC/PKC signalling pathway, while group I mGluR inhibition of I-GIRK occurs via the PLA(2)-dependent production of arachidonic acid. These results present a novel receptor-specific mechanism for crosstalk between G(q)PCRs and GABA(B) receptors.
Keywords: RECTIFYING POTASSIUM CHANNEL; SHORT-TERM DESENSITIZATION; PHOSPHOLIPASE-C ISOZYMES; MOUSE ATRIAL MYOCYTES; PROTEIN-KINASE-C; PHOSPHATIDYLINOSITOL 4,5-BISPHOSPHATE; MEDIATED INHIBITION; ARACHIDONIC-ACID; CA3 NEURONS; FATTY-ACIDS